Factors Associated with Overcrowded Emergency Rooms in Thailand: A Medical School Setting - Arrug Wibulpolprasert; Yuwares Sittichanbuncha; Pungkava Sricharoen; Somporn Borwornsrisuk; Kittisak Sawanyawisuth (Emergency Medicine International)
Background. Overcrowding in the emergency department (ED) is a significant public health problem in the US, Europe, and Asia. Factors associated with prolonged length of stay in Thailand are still limited. Methods. This study was conducted at the ED, Ramathibodi Hospital, Mahidol University, Thailand, during July 2011. We selected 300 patients (5.77%) from a total of 5,202 who visited the ED during the study period by simple random sampling. Charts were retrospectively reviewed baseline characteristics, clinical factors, and duration of ED stay. Multivariate logistic regression analyses were performed to identify independent factors for an ED stay more than or equal to 8 hours. Results. We excluded 33 patients (11%) due to incomplete data or stroke fast track enrollment. In total, 267 patients were in the analysis and 53 patients (19.85%) had an ED visit time more than or equal to 8 hours. The number of rounds of blood testing and the type of insurance were associated with prolonged ED stay of more than or equal to 8 hours. Conclusion. ED physicians may need to consider appropriate investigations to shorten the length of stay in the ED.